RACIAL AND ETHNIC DIFFERENCES IN THE NEIGHBORHOOD CONTEXT OF MASTERY. Issue 1 (January 2016) - Gilster, Megan E.
Abstract : Residents of poor, non‐white neighborhoods experience high rates of neighborhood stressors like crime, violence, and disorder. Stress process theory suggests that mastery is important for understanding how neighborhood stressors affect resident mental health. This research examines the relationship between neighborhood stressors and mastery with a focus on racial and ethnic differences in a multi‐ethnic sample of Chicago residents. Because Black and Hispanic residents disproportionately live in high stressor neighborhoods and have more difficulty escaping them than Whites, a compound disadvantage model is proposed and tested using multilevel models with cross‐level interactions. Findings suggest race‐specific neighborhood antecedents of mastery and support for the compound disadvantage hypothesis. In highest stress neighborhoods, Blacks have lower mastery than Whites. In average and lower stress neighborhoods, Blacks have a mastery advantage.